Hooked on technology: examining the co-occurrence of nomophobia and impulsive sensation seeking among nursing students - El-Ashry, Ayman Mohamed; El-Sayed, Mona Metwally; Elhay, Eman Sameh Abd; Taha, Samah Mohamed; Atta, Mohamed Hussein Ramadan; Hammad, Heba Abdel-Hamid; Khedr, Mahmoud Abdelwahab (BMC nursing, 2024)
Background Nomophobia, the crippling fear of being disconnected from mobile devices, is a burgeoning global concern. Given the critical nature of the profession of nursing students, understanding nomophobia’s prevalence and potential impacts on patient care and professional conductors becomes even more crucial. Aim This study explores the relationship between nomophobia and impulsive sensation-seeking among nursing students in Egypt. Design and methods A multicenter cross-sectional survey was conducted with 1626 nursing students randomly selected from three universities across Egypt. Tools The Arabic versions of the Nomophobia and Impulsive Sensation Seeking Questionnaires were employed to gather data. Results Our findings revealed that 40.3% of the surveyed nursing students exhibited severe nomophobia, indicating a substantial dependence on their mobile devices. Notably, this high prevalence was accompanied by a strong tendency towards impulsive sensation-seeking behaviors. Furthermore, a stepwise regression analysis identified several significant predictors of nomophobia ( p < 0.001). Impulsive sensation-seeking, year of study, average daily smartphone usage, and age emerged as key factors, explaining 27.5% of the variability in nomophobia scores. Conclusion The prevalence of nomophobia among Egyptian nursing students is undeniable, highlighting their substantial reliance on mobile devices. A significant association with impulsive sensation-seeking behavior further compounds this dependence. Factors such as impulsive sensation seeking, year of study, average daily smartphone usage, and age were identified as significant predictors of nomophobia. Recognizing these factors as key predictors of nomophobia is crucial for designing effective interventions and psychotherapies. Prioritizing such interventions can promote future nurses’ well-being and ensure they deliver the highest quality care to their patients.